AB0951 Factors associated with response to adalimumab treatment in juvenile idiopathic arthritis. (15th June 2017) - Kashchenko, E; Alexeeva, E; Bzarova, T; Valieva, S; Denisova, R; Lomakina, O; Isaeva, K; Soloshenko, M; Karaseva, A
Abstract : Background: Tumor necrosis factor inhibitors are highly effective and safe in treatment of juvenile idiopathic arthritis (JIA). Nonetheless, to select the optimal therapy and to achieve maximum therapeutic effect it is necessary to consider the individual characteristics of the patient. Adalimumab (ADA) is widespread use for mild and severe polyarticular JIA especially in the presence of uveitis, but there is lack of data about clinical and laboratory predictors of response to ADA in different JIA categories. Objectives: To identify clinical and laboratory parameters associated with response to adalimumab treatment in 12 months in patients with different JIA category. Methods: Analysis include patients with enthesitis-related arthritis (ERA, n=56), RF-negative polyarthritis (polyRF-, n=50), extended oligoarthritis (extOligo, n=30), and persistent oligoarthritis (persOligo, n=62) with median age 10.5 (IQR 7–14) and median JADAS-71 19.5 (IQR 15–28). Patients were divided to response groups after 12 month treatment with ADA according to ACRPedi criteria, achieving inactive disease by Wallace criteria and JADAS-71 cut-off point as excellent, intermediate and poor responders. For each of JIA category univariate and multivariate logistic regression analysis was conducted to identify potential baseline factors associated with treatment response. Baseline factors included clinical, laboratory and anamnestic data. Results: ADA was shown to be effective in all groups with 90%/89%/82%/63% children with ACR30/50/70/90 during one year therapy. The most significant factors (p<0.05) associated with response to ADA treatment are presented in summarized table. Our findings demonstrated that different predictors corresponded with different JIA categories. Interestingly subjective scales of disease activity was shown to be strongly associated with response to therapy. At the same time VAS severity at baseline were inversely correlated with achievement of good response. Duration of morning stiffness correlated with excellent response in children with 2 different categories. However, for ERA patients shorter duration was associated with better response to treatment while vice versa for PersOligo patients. Conclusions: Predictors of response to ADA treatment differ in JIA categories. Low disease activity parameters (clinical and laboratory) at baseline not always predict good response to therapy. Disclosure of Interest: E. Kashchenko Grant/research support from: Novartis, E. Alexeeva Grant/research support from: Roche, Abbott, Pfizer, Bristol-Myers Squibb, Centocor, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Bristol-Myers Squibb, Medac, Novartis, Pfizer, T. Bzarova Grant/research support from: Roche, Pfizer, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Pfizer, S. Valieva Grant/research support from: Roche, Bristol-Myers Squibb, Speakers bureau: Roche, Merck Sharp & Dohme, Bristol-Myers Squibb, Medac, Novartis, R. Denisova Grant/research support from: Roche, Centocor, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Medac, O. Lomakina: None declared, K. Isaeva Grant/research support from: Roche, Novartis, M. Soloshenko: None declared, A. Karaseva: None declared